1984
DOI: 10.3758/bf03206354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration on detection by the chromatic and achromatic systems

Abstract: and MICHAEL S. LOOP University ofAlabama, Birmingham, AlabamaDetectability was determined as a function of stimulus duration for the chromatic and achromatic systems. For the achromatic system, detectability remains relatively constant for durations ranging from 43 to 1,000 msec, whereas for the chromatic system, detectability increases with duration up to about 500 msec. This suggests that the chromatic system has a more sustained output than the achromatic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These units are found at all levels of the auditory pathway, and may be organized into functional systems, resulting in differential processing of transient and sustained stimulus attributes. In this respect, the LTC and STC systems are analogous to Pacinian and non-Pacinian systems in tactile processing (Gescheider, 1976;Verrillo, 1968), and to chromatic (X-cell) and achromatic (Y-cell) systems in visual processing (Schwartz & Loop, 1984). All three modalities illustrate distinctive transient and sustained systems which possess different temporal summation properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These units are found at all levels of the auditory pathway, and may be organized into functional systems, resulting in differential processing of transient and sustained stimulus attributes. In this respect, the LTC and STC systems are analogous to Pacinian and non-Pacinian systems in tactile processing (Gescheider, 1976;Verrillo, 1968), and to chromatic (X-cell) and achromatic (Y-cell) systems in visual processing (Schwartz & Loop, 1984). All three modalities illustrate distinctive transient and sustained systems which possess different temporal summation properties.…”
Section: Discussionmentioning
confidence: 99%
“…A stimulus with both transient and sustained properties may activate both types of response system. This transientsustained dichotomy has been found for auditory (Graham, 1979), tactile (Verrillo, 1968), and visual (Schwartz & Loop, 1984) inputs, and underlying neurological mechanisms have been proposed in each modality (Gersuni, 1971;Gescheider, 1976;Hickey, 1977).…”
mentioning
confidence: 91%
“…On the basis ofthe identification of transient (short time constant) and sustained (long time constant) neural types in the auditory system (Gersuni, 1971;Gersuni et aI., 1971), Graham (1979) has suggested that these transient and sustained stimulus parameters may be processed by parallel neurological systems. Transient and sustained systems in the auditory pathway are analogous to Y cells and X cells (retinal ganglion cells) in the visual system (Schwartz & Loop, 1984), and to Pacinian and non-Pacinian systems in the vibrotactile modality (Gescheider, Hoffman, Harrison, Travis, & Bolanowski, 1994). Several researchers (Graham & Murray, 1977;Ison, 1978) state that startle elicitation is due to the activation of the transient system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, transient-sensitive neurons are thought to function as stimulus detectors and sustained-sensitive neurons are thought to function as stimulus analyzers or "discriminators" Berg, 1985!. Similar short time and long time constant neurons have also been found for visual and tactile stimuli~Breitmeyer & Ganz, 1976;Gescheider, Hoffman, Harrison, Travis, & Bolanowski, 1994;Schwartz & Loop, 1984!. It has been hypothesized that acoustic elicitation of startle and PPI are controlled by the activation of short time constant neurons Graham & Murray, 1977!. Several studies have supported the hypothesis that the transient system makes the greatest contribution to PPI~Blumenthal & Levey, 1989;Graham & Murray, 1977;Lane, Ornitz, & Guthrie, 1991!. These studies compared the effectiveness of discrete prepulses~brief, nonstartling stimuli that terminate before the startle stimulus is presented!…”
mentioning
confidence: 86%